Associations of Accelerometer‐Measured Sedentary Time and Physical Activity With Prospectively Assessed Cardiometabolic Risk Factors: The CARDIA Study. Issue 1 (8th January 2019) - Whitaker, Kara M.; Pettee Gabriel, Kelley; Buman, Matthew P.; Pereira, Mark A.; Jacobs, David R.; Reis, Jared P.; Gibbs, Bethany Barone; Carnethon, Mercedes R.; Staudenmayer, John; Sidney, Stephen; Sternfeld, Barbara
Abstract : Background: Isotemporal substitution examines the effect on health outcomes of replacing sedentary time with light‐intensity physical activity or moderate‐to‐vigorous intensity physical activity; however, existing studies are limited by cross‐sectional study designs. Methods and Results: Participants were 1922 adults from the CARDIA (Coronary Artery Risk Development in Young Adults) study. Linear regression examined the associations of sedentary, light‐intensity physical activity, and moderate‐to‐vigorous intensity physical activity at year 20 (2005–2006) with waist circumference, blood pressure, glucose, insulin, triglycerides, high‐density lipoprotein cholesterol, and a composite risk score at year 30 (2015–2016). Models then examined change in activity with change in cardiometabolic risk over the same 10‐year period. Replacing 30 min/day of sedentary time with 30 min/day of light‐intensity physical activity at year 20 was associated with a lower composite risk score (−0.01 SD [95% CI, −0.02, −0.00]) at year 30, characterized by lower waist circumference (0.15 cm [95% CI, −0.27, 0.02]), insulin (0.20 μU/mL [95% CI, −0.35, −0.04]), and higher high‐density lipoprotein cholesterol (0.20 mg/dL [95% CI, 0.00, 0.40]; all P <0.05). An increase of 30 min/day in MVPA from year 20 to year 30, when replacing an equivalent increase in sedentary time, was associated with a decrease in the composite risk score (−0.08 [95% CI, −0.13, −0.04]) over the same 10 years, characterized by a decrease in waist circumference (1.52 cm [95% CI, −2.21, −0.84]), insulin (−1.13 μU/mL [95% CI, −1.95, −0.31]), triglycerides (−6.92 mg/dL [95% CI, −11.69, −2.15]), and an increase in high‐density lipoprotein cholesterol (1.59 mg/dL [95% CI, 0.45, 2.73]; all P <0.05). Conclusions: Replacement of sedentary time with light‐intensity physical activity or moderate‐to‐vigorous intensity physical activity is associated with improved cardiometabolic health 10 years later.